Reflection on conformism - Szabała, Henryk (Folia Philosophica, 2002)
The author treats conformism as a prerequisite for one’s adaptation to life in the world. The key notion here is the category, introduced by the author, of the “co-fonn”, for a conformist is a person who always creates his or her special “co-form” with the world in which they happen to live. The author perceives the source of conformism to reside in people’s desire for social approval. The article takes into account also the role of conformism in the wielding of power.